Bioassay complexities—exploring challenges in aquatic chemosensory research - Hardege, Jorg D.; Fletcher, Nichola; Burnett, Jonathan W.; Ohnstad, Hannah; Bartels-Hardege, Helga D. (Frontiers in Ecology and Evolution, 2024)
Chemosensory science, the study of how organisms produce and assess olfactory information, is central to our understanding of how organisms interact and gain information about their environment. Signaling cue identification in aquatic systems lags behind our knowledge in terrestrial insects due to analytical challenges in aqueous environments. Unambiguous, reliable, and fast behavioral assays to evaluate the biological activity and function of a chemosensory cue are critical to understand aquatic signaling systems and enable research into their ecology, evolution, and threats in a changing environment. Yet, a range of anthropomorphic assumptions made in this research field create additional challenges to interpret data generated. Here, we evaluate common challenges including assumed readiness of individuals to respond, lack of information on the animals’ physiological and social status, their pre-experimental cue exposure, the innate or learned character of the responses, the animals’ acclimation and habituation status, and the impact of the animals upon their own environment. These factors lead to significant variability in animals’ responses in bioassays, both in the field and in laboratory setups. In the light of our limited knowledge of aquatic chemosensory cues’ chemical structure, active concentrations in samples, and undetermined response thresholds, we evaluate methods of mitigation to minimize differences between studies. We conclude that currently it is nearly impossible to compare results from chemosensory behavioral studies undertaken in different ecosystems, laboratories, and time points. There is an urgent need for the standardization of behavioral methods, recording of environmental conditions, and individuals’ physiology, physical, and social status, to avoid conflicting and contradicting results when comparing studies. Including these parameters in experimental design and data interpretation will provide a deeper understanding of chemosensory communication, reduce unconscious bias in studies, and can help to explain the substantial individuality in animals’ responses to chemosensory cues and their acclimation to environmental stress.